Reality-show: inheritances in genre hybridization - Mateus, Samuel (2012)
Trying to answer reality-show’s problems of classification, this paper argues that, nevertheless reality-show’s constitutive multiplicity, diversity of formats and fluid nature, it is possible to delimit its general outlines as a television genre. As a first step to this task, we will emphasize a set of influences and factors that have contributed decisively to shape what we mean today by reality-show, namely, the artistic movements of realism and naturalism, the tabloid journalism, the documentary aesthetic, and the development of television as an industry.